Measuring the returns to education the case study of the Cordillera Administrative Region - Aguila, Lara Bianca B. (2013)
Education plays a key determining the earnings of an individual. As educational attainment rises, earnings increase with it. In the Cordillera Administrative Region, the earnings gap between the less educated and the better educated are high as majority of its labor force are college graduates.Using the October round of the 2011 Labor Force Survey, this research measures the private returns to education for the different levels of education, the increase in average monthly earnings for each major occupation group, and the disparities in earnings for males and females, and urban and rural workers. the empirical results show that returns to education increase with educational attainment. For all samples, elementary graduates, high school, and college graduates earn 2.02 percent, and 13.50 percent more compared to those with no education.The results also show that there are gender and spatial differences in earnings. Males receive higher earnings that females. Also, the magnitude of the increase in earnings for every increase in educational attainment is larger for males. Urban workers receive higher earnings than rural workers but the latter collects larger increase in earnings for every increase in the level of education. Therefore, there is a need to improve the quality of education and standardized the education system that is accepted internationally to remove the inequality in earnings and to produce globally competitive workers --Authors Abstract.